2005
DOI: 10.1182/blood-2004-09-3740
|View full text |Cite
|
Sign up to set email alerts
|

B-cell kinetics in humans: rapid turnover of peripheral blood memory cells

Abstract: Information about the kinetic behavior and lifespan of lymphocytes is crucial to understanding the mechanisms that regulate processes such as immunologic memory. We have used in vivo labeling of dividing cells with 6,6-2 H 2 -glucose, combined with cell sorting and gas-chromatography-mass spectrometry for deuterium enrichment, in order to analyze the kinetics of human total, naive, or memory B lymphocytes, separated from peripheral blood using monoclonal antibodies. We show that total blood B cells of young ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
114
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(140 citation statements)
references
References 54 publications
25
114
1
Order By: Relevance
“…In the spleen, increases in GFP marking over time were seen for CD19 1 and Gr-1 1 cells, suggesting an influx of modified cells derived from HSPCs in the BM, rather than initial transduction or expansion of the cells in the spleen. The fact that the CD19 1 cells turnover is less than 4 weeks 21,22 and that modified cells are detected at much later time points, support this hypothesis. Notably, changes in the levels of BM CD19 1 and Gr-1 1 cells were observed after in vivo transduction, independent of animals' mobilization status.…”
Section: Resultssupporting
confidence: 69%
“…In the spleen, increases in GFP marking over time were seen for CD19 1 and Gr-1 1 cells, suggesting an influx of modified cells derived from HSPCs in the BM, rather than initial transduction or expansion of the cells in the spleen. The fact that the CD19 1 cells turnover is less than 4 weeks 21,22 and that modified cells are detected at much later time points, support this hypothesis. Notably, changes in the levels of BM CD19 1 and Gr-1 1 cells were observed after in vivo transduction, independent of animals' mobilization status.…”
Section: Resultssupporting
confidence: 69%
“…Using in vivo labeling of dividing cells, cell sorting, and gas chromatography-mass spectrometry, the authors showed that naive B cells divide slowly (0.46% per day), whereas memory B cells proliferate more rapidly (2.66% per day). This supports the view that B cell memory may be maintained independently of Ag by clones of spontaneously proliferating B cells (47).…”
Section: Menc-specific Memory B Cell Immune Responses Postboostersupporting
confidence: 77%
“…Consequently, this theory suggests that memory B cells continuously recirculate through the blood and secondary lymphoid organs (27), and therefore circulating levels of Ab are in proportion to the total Ag-specific memory B cell pool that is reflected by the frequency of circulating Ag-specific B cells. This theory is supported by a B cell kinetic study in humans (47). Using in vivo labeling of dividing cells, cell sorting, and gas chromatography-mass spectrometry, the authors showed that naive B cells divide slowly (0.46% per day), whereas memory B cells proliferate more rapidly (2.66% per day).…”
Section: Menc-specific Memory B Cell Immune Responses Postboostersupporting
confidence: 54%
“…This is consistent with the idea that antigen persistence and continuous stimulation are necessary to maintain memory B-cells [25]. However, to date, polysaccharides were not thought to be able to elicit a memory B cell response [26].…”
Section: Microanatomic Site Of Splenic Immune Reaction Towards Polysasupporting
confidence: 85%